DICTOGLOSS IN IMPROVING LISTENING COMPREHENSION - Widhiasih, Luh Ketut Sri (Yavana Bhasha : Journal of English Language Education, 2019)
The objective of this classroom action research was to know whether or not listening comprehension of the Basic Listening class students of English Language Education Study Program, Faculty of Teacher Training, Mahasaraswati Denpasar University academic year 2016/2017 can be improved through dictogloss technique. The present research was carried out through dictogloss technique in two cycles; each cycle consisted of two sessions. The data were collected by administering the instruments to the subjects. The result of the post test in each cycle showed that there was significant improvement of the subjects’ comprehension in listening. The subjects also gave positive responses toward the implementation of dictogloss technique in teaching and learning process. To sum up, the present classroom action research showed that listening comprehension of the Basic Listening class students of English Language Education Study Program, Faculty of Teacher Training, Mahasaraswati Denpasar University academic year 2016/2017 can be improved through dictogloss technique.